Relationship between right-to-left shunt and white matter lesions in patients with migraine: a single-center study - Liu, Zhihong; Jiang, Mingzhu; He, Jing; Lin, Yuchan; He, Lou; Li, Yan; Pan, Qi; Wu, Shan (Frontiers in Neurology, 2024)
Background Migraine patients have an increased long-term risk of cardio and cerebrovascular events. However, whether these patients are more susceptible to white matter lesions (WMLs) remains debated. To explore this question, our study assessed the proportion of RLS in migraine patients and explored the association between right-to-left shunt (RLS) and WMLs. Methods In this study, we included 998 migraine patients. Contrast transcranial doppler (c-TCD) was used to diagnose RLS and assess the extent of the shunt in RLS patients. Of the 998 patients, 505 underwent cranial magnetic resonance imaging (MRI) assessments. WMLs were classified into periventricular white matter lesions (pvWMLs) and deep white matter lesions (dWMLs). Results Among the 998 migraine patients, 946 had migraine without aura (MO; mean age 36.68 ± 10.46 years; 80.5% female), and 52 had migraine with aura (MA; mean age 29.85 ± 8.59 years; 71.2% female). Compared with MO patients, MA patients had an earlier onset age (23.1 ± 7.97 vs. 28.44 ± 10.38 years, p < 0. 001) and a shorter disease duration (6.76 vs. 8.34 years, p = 0.024). The overall proportion of RLS patients was 41.9%, with a greater proportion of RLS patients in the MA group than in the MO group (55.8% vs. 41. 1%, p = 0.037). The percentage of RLS-positive patients with no/small shunt was greater in the MO group than in the MA group (81.5% vs. 65.4%, p = 0.004), whereas the percentage of RLS-positive patients with moderate/large shunt was greater in the MA group (34.6% vs. 18.5%, p = 0.024). The proportion of RLS patients was lower in the WML-positive group (n = 173) than in the WML-negative group (n = 332), but the difference was not significant (40.5% vs. 45.8%, p = 0.253). Conclusion This study revealed that 41.9% of migraine patients had RLS, and the proportion of RLS patients was 41. 1% in the MO group and 55.8% in the MA group. The rate of RLS positivity in migraine patients may not be related to the incidence of WMLs.